Inhibition of miR-208b improves cardiac function in titin-based dilated cardiomyopathy - Zhou, Qi-Feng; Sticht, Carsten; Labeit, Siegfried (International journal of cardiology, 2017)
Background: Dilated cardiomyopathy (DCM) is the result of maladaptive cardiac remodeling, which involves microRNA regulation. In turn, microRNAs can contribute to the remodeling process by post-transcriptional modulation of gene expression networks. The exact role of microRNAs in the pathogenesis of DCM is largely unknown. Here, we used an inducible DCM mouse model that carries a human truncation mutation in the sarcomeric protein titin to dissect microRNA pathways in DCM development. Methods and results: MicroRNA microarray studies revealed up-regulation of microRNA-208b in the myocardium of DCM mice and DCM patients (p<0.05 compared to controls). In order to investigate the effect of microRNA-208b on cardiac remodeling, loss-of-function and gain-of-function studies were performed by repetitive injections of LNA-modified microRNA-208b mimics and antimiR-208b. MiR-208b overexpression resulted in cardiac hypertrophy, whereas miR-208b antagonisation prevented transition of adaptive to maladaptive remodeling in the DCM mouse model. In vitro studies identified several pro-hypertrophic transcription factors as potential targets of miR-208b, suggesting that microRNA-208b plays an important role in cardiac development and growth. MiR-208b was also upregulated in DCM patients, but not in heart failure patients due to ischemic heart disease or myocarditis. Conclusion: Our data suggests that miR-208b is involved in the remodeling process and pathogenesis of DCM by post-transcriptional gene expression modulation. MicroRNA-208b might be a novel therapeutic target for DCM.